2016
DOI: 10.1111/fwb.12752
|View full text |Cite
|
Sign up to set email alerts
|

Increasing fish taxonomic and functional richness affects ecosystem properties of small headwater prairie streams

Abstract: Summary Stream fish can regulate their environment through direct and indirect pathways, and the relative influence of communities with different taxonomic and functional richness on ecosystem properties likely depends on habitat structure. Given this complexity, it is not surprising that observational studies of how stream fish communities influence ecosystems have shown mixed results. In this study, we evaluated the effect of an observed gradient of taxonomic (zero, one, two or three species) and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 53 publications
4
23
0
Order By: Relevance
“…Mobile animals may be forced into the upper, oxygenated pool where they are more prone to predation, whereas plants and microbes must simply adjust to transient low O 2 concentrations. Fishes may congregate in the shallow pools and increase metabolic activity (Martin et al, 2016), at least until oxygen is depleted. Trophic complexity can increase N uptake (Bernot, Martin & Bernot, 2010a) and thus metabolism rates.…”
Section: Figmentioning
confidence: 99%
“…Mobile animals may be forced into the upper, oxygenated pool where they are more prone to predation, whereas plants and microbes must simply adjust to transient low O 2 concentrations. Fishes may congregate in the shallow pools and increase metabolic activity (Martin et al, 2016), at least until oxygen is depleted. Trophic complexity can increase N uptake (Bernot, Martin & Bernot, 2010a) and thus metabolism rates.…”
Section: Figmentioning
confidence: 99%
“…Several other studies have similarly shown that herbivorous fish can reduce periphyton, both on a small scale (e.g. Flecker et al., 2002; Martin et al., 2016; Schneck et al., 2013; Veach et al., 2018; Wootton & Oemke, 1992) and on a mesohabitat scale (Gelwick & Matthews, 1992; Power et al., 1985,1989; Stewart, 1987). However, compared to the mean hyporheic oxygen concentration, which was more than twice as high in enclosures stocked with nase than in those without fish stocking, the reduction in the mean AFDM was rather small.…”
Section: Discussionmentioning
confidence: 91%
“…In North and South American streams, strong direct effects of herbivorous fish on periphyton have been observed both in small‐scale experiments (Flecker et al., 2002; Martin, Gido, Bello, Dodds, & Veach, 2016; Schneck, Schwarzbold, & Melo, 2013; Veach, Troia, Jumpponen, & Dodds, 2018; Wootton & Oemke, 1992) and on a mesohabitat scale (Gelwick & Matthews, 1992; Power, Dudley, & Cooper, 1989; Power, Matthews, & Stewart, 1985; Stewart, 1987). Grazing fish were also shown to reduce the filament lengths of filamentous green algae (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such it is also likely to be of general importance to the functional integrity and productivity of many if not most northern lacustrine ecosystems (e.g. Martin, Gido, Bello, Dodds, & Veach, 2016). To take SIPD into account in general conservation policy and local conservation initiatives (Poulin & Pérez-Ponce de León, 2017), it is necessary to understand its full extent and nature in lakes, as well as its evolutionary origins and significance.…”
Section: Conservation Implicationsmentioning
confidence: 99%